Bibliometric overview of operations research/management science research in Turkey - Bilir, Canser; Güngör, Cengiz; Kökalan, Özgür; Kökalan, Özgür (Yildiz Technical Univ, 2019)
This paper provides a bibliometric analysis of the articles in the field of Operations Research - Management Science (OR / MS) published between the years 1980- 2017 by researchers from Turkey. The main objective of the analysis is to identify and examine the current state of OR / MS studies in Turkey. The analysis is conducted based on the data from the Web of Science (WoS) databases: Science Citation Index Expanded (SCI-Expanded), Social Sciences Citation Index (SSCI), Arts & Humanities Citation Index (A&HCI), Science Citation Index (SCI), and Emerging Science Citation Index (ESCI). We found a total of 3,433 papers in 101 different journals in field of OR / MS by researchers from Turkey. The results provide a general picture of the studies classified by the most influential authors, institutions, papers, and journals. The analysis also provided citation statistics of the OR / MS articles in Turkey. The current research trends are identified through an analysis of keywords through years. In the paper the collaboration with foreign countries and institutions are also identified through a collaboration analysis.
WOS:000488302000009
Keywords: Operation research or management science publication; Turkey; bibliometric; Web of Science (WoS)